Pullulan Based Bioconjugates for Ocular Dexamethasone Delivery - Eva Kicková; Stefano Salmaso; Francesca Mastrotto; Paolo Caliceti; Arto Urtti (MDPI AG, 2021)
Posterior segment eye diseases are mostly related to retinal pathologies that require pharmacological treatments by invasive intravitreal injections. Reduction of frequent intravitreal administrations may be accomplished with delivery systems that provide sustained drug release. Pullulan-dexamethasone conjugates were developed to achieve prolonged intravitreal drug release. Accordingly, dexamethasone was conjugated to ~67 kDa pullulan through hydrazone bond, which was previously found to be slowly cleavable in the vitreous. Dynamic light scattering and transmission electron microscopy showed that the pullulan-dexamethasone containing 1:20 drug/glucose unit molar ratio (10% w/w dexamethasone) self-assembled into nanoparticles of 461 ± 30 nm and 402 ± 66 nm, respectively. The particles were fairly stable over 6 weeks in physiological buffer at 4, 25 and 37 °C, while in homogenized vitreous at 37 °C, the colloidal assemblies underwent size increase over time. The drug was released slowly in the vitreous and rapidly at pH 5.0 mimicking lysosomal conditions: 50% of the drug was released in about 2 weeks in the vitreous, and in 2 days at pH 5.0. In vitro studies with retinal pigment epithelial cell line (ARPE-19) showed no toxicity of the conjugates in the cells. Flow cytometry and confocal microscopy showed cellular association of the nanoparticles and intracellular endosomal localization. Overall, pullulan conjugates showed interesting features that may enable their successful use in intravitreal drug delivery.